Insights and research trends in active aging technologies: a bibliometric review study - Smal, Yulia (2024)
This bibliometric analysis explores the evolution of active aging technologies over the past decade, examining key research performance metrics, the most influential authors, studies, sources, and the international collaboration network. The technologies reviewed include both software and hardware solutions—such as e-health platforms, wearable devices, assistive robotics, and smart home systems among others —designed for direct use by end-users (older adults or their caregivers). The findings highlight interdisciplinary contributions from fields like medicine, engineering, and social sciences, along with strong international collaboration, underscoring a collective effort to enhance the quality of life for older adults.